Evaluation of physico-chemical and biological properties of calcium hydroxide associations - Cesario, Francine (2019)
This study aimed to evaluate various properties of pastes that associated NSAIDs and antibiotics with calcium hydroxide (CH). Five groups were analyzed: G1: CH + propylene glycol; G 2: CH + 5% sodium diclofenac + propylene glycol; G3: CH + 5% amoxicillin + propylene glycol; G4: CH + 5% ibuprofen + propylene glycol; and G5: CH + 5% metronidazole + propylene glycol. Root canals of acrylic teeth (n = 10 / group) were filled with the pastes and scanned by computerized microtomography before (initial) and after 7, 15 and 30 days of immersion in ultrapure water to evaluate the solubility of the pastes. The pH and calcium ion release in this water were determined through a pH meter and an atomic absorption spectrophotometer, respectively. An E. Faecalis biofilm and a mixed E. faecalis and Pseudomonas aueruginosa biofilm were induced in dentin blocks (n = 4 / biofilm). The blocks were then distributed and immersed in the experimental pastes for 7 days to determine antimicrobial action. To evaluate microbial adhesion, bovine dentin blocks were placed in petri dishes and then covered with pastes and placed in a greenhouse at 37ºC for 7 days. Afterward, the specimens were contaminated for one hour using the bacterium E. faecalis. Through the live/dead dye and a confocal laser scanning, microscope images were captured and the percentage of viable and non-viable bacterial cells determined. The pastes were also inserted into plates containing macrophages adhered for 24 hours. The analysis of nitric oxide (NO) production by these cells was performed by Greiss reaction. Data were statistically compared ( <0.05). The results showed that the highest release of hydroxyl ions was observed within 30 days for group G1 (P <0.05). The release of calcium ions was higher in group G5 within 7 days (P <0.05). All groups had a similar mass loss and antimicrobial action against mixed biofilm (P> 0.05). In E. faecalis biofilm the highest antimicrobial action was observed in group G5 (P <0.05) followed by G4 (P <0.05), as well as for adhesion of M.O and release of NO. All groups were statistically different from the positive control in all tests (P <0.05). Associations of NSAIDs with calcium hydroxide did not interfere with pH, calcium ion release and solubility. Combinations of NSAIDs and antibiotics contributed to the antimicrobial action of calcium hydroxide paste. The use of metronidazole increased the adhesion of E. faecalis bacterial cells to dentin and the production of nitric oxide by macrophages.